REGISTER SUPORTER PSS SLEMAN - Muhammad Ken Narendhra; Icuk Prayogi; Rawinda Fitrotul Mualafina ((JIBS) JURNAL ILMIAH BAHASA DAN SASTRA, 2025)
This study aims to describe the forms, formation processes, and functions of register used by PSS Sleman supporters, particularly the Brigata Curva Sud (BCS) community. This research employs a descriptive qualitative method. The data were collected through observation, note-taking, recording, and documentation, sourced from chants, conversations, supporter attributes, and social media. The data were analyzed using referential and pragmatic analysis methods based on Halliday’s theory of register. The results indicate that the registers used by PSS Sleman supporters appear in the forms of words, acronyms, and abbreviations, such as PSS Per Sempre, Vinci Per Noi, Laskar Sembada, PSS Siamonoi, Ora Muntir, Curva Sud, Super Elja, and BCS. These registers are formed through borrowings from English, Italian, and Javanese. English is used to express universal loyalty, Italian reflects the influence of European ultras culture, while Javanese emphasizes local identity. In terms of function, the register serves as a marker of group identity, a marker of style, and a means of concealing information from outsiders. Overall, register plays an important role in strengthening solidarity, maintaining group cohesion, and shaping the collective identity of PSS Sleman supporters as part of Indonesian football culture.